PSVI-39 Administration of intramuscular progesterone and eCG to induce estrus activity in anovulatory goats under an intensive production system. - Zúñiga, S (J Anim Sci, 2018)
The aim of this study was to evaluate the efficiency of intramuscular progesterone and equine chorionic gonadotropin (eCG) administration to induce estrus activity in anovulatory goats. In March, mix-bred dairy goats (n=70; 26° north) were randomly allocated in two groups homogenous regarding body weight (41.86 ± 1.08 kg) and body condition score (1.87 ± 0.04). Every goat received 25 mg of progesterone and 24 h later were exposed to two intramuscular hormonal treatments: 1). 350 IU of eCG (T350; n=35) and 100 IU of eCG (T100; n=35). Then, 12 h after eCG administration, both groups were exposed to active males (n=7; 0800 & 1800 h x 15 min x 7d) and estrus activity was evaluated considering the percentage of females in estrus, estrus latency and estrus length. While the percentage of estrus females was analyzed with a Chi square test, estrus latency and estrus length were analyzed using an ANOVA with a Tukey test. No differences (P>0.05) occurred between treatments for estrus percentage and estrus length (T350; 77%, 30.67 ± 3.09 and T100; 74%; 27.23 ± 2.26). Regarding estrus latency, differences occurred between treatments (P<0.01; T350 57.78 ± 2.31 and T100; 76.15 ± 3.26). Results demonstrated that administration of 25 mg intramuscular progesterone, followed by a dose of 100IU of eCG, can be effectively used to induce estrus activity in dairy goats managed in an intensive system, decreasing the amount of hormones used as well as the economic cost.